IMPLEMENTATION OF DIVIDE AND CONQUER IN THE HANOI TOWER GAME - Bonifacius Vicky Indriyono; Zudha Pratama (Universitas Dian Nuswantoro and IndoCEISS, 2020)
Artificial Intelligence (AI) is a technology in the field of computer science that simulates human intelligence into computers to solve various problems and jobs as well as humans do. Games / games are an implementation of the field of computer science which also embraces the concept of AI. In the midst of the rampant types of games available, the author chose the Hanoi Tower which is a mathematical game / puzzle that requires logic. Players are challenged to complete in a short time with a certain number of discs. The benefit of this game is that it can train how to think with certain patterns so as to improve the memory of players. To make it easier to solve it, the Divide and Conquer Algorithm can be used which can solve problems in the Tower of Hanoi game by breaking them down into sub-problems which will later be able to help speed up finding solutions. From the results of testing the application of the Divide and Conquer Algorithm in the hanoi tower game application by solving the disk arrangement problem. Players can finish the game in a large number of plates in a short time. Keywords – Artificial Intelligence, Divide and Conquer Algorithm, Games, Tower of Hanoi.